2013
DOI: 10.1155/2013/730131
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune Cytopenias in Chronic Lymphocytic Leukemia

Abstract: The clinical course of chronic lymphocytic leukemia (CLL) may be complicated at any time by autoimmune phenomena.The most common ones are hematologic disorders, such as autoimmune hemolytic anemia (AIHA) and immune thrombocytopenia (ITP). Pure red cell aplasia (PRCA) and autoimmune agranulocytosis (AG) are, indeed, more rarely seen. However, they are probably underestimated due to the possible misleading presence of cytopenias secondary to leukemic bone marrow involvement or to chemotherapy cytotoxicity. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 73 publications
0
12
0
Order By: Relevance
“…Older age, male gender correlated with the development of ITP [14]. It was reported that IC is more common in patients with unmutated IGHV status [23,24]. It is considered that a high level of β2-microglobulin [24,25], increased CD 38 [22,25], high ZAP70 [24,26,27,28] may be antecedents of IC.…”
Section: Resultsmentioning
confidence: 99%
“…Older age, male gender correlated with the development of ITP [14]. It was reported that IC is more common in patients with unmutated IGHV status [23,24]. It is considered that a high level of β2-microglobulin [24,25], increased CD 38 [22,25], high ZAP70 [24,26,27,28] may be antecedents of IC.…”
Section: Resultsmentioning
confidence: 99%
“…Cytokines production from CLL cells can result in inhibition of normal erythropoiesis or megakaryopoiesis, leading to development of AIHA or ITP [14]. CLL cells can rarely act as effector cells, secreting a pathological monoclonal antibody [15]. CLL cells may also be stimulated through their polyreactive B-cell receptor (BCR) that recognizes autoantigens [15].…”
Section: Discussionmentioning
confidence: 99%
“…CLL cells can rarely act as effector cells, secreting a pathological monoclonal antibody [15]. CLL cells may also be stimulated through their polyreactive B-cell receptor (BCR) that recognizes autoantigens [15].…”
Section: Discussionmentioning
confidence: 99%
“…The expansion of these B-cells is associated with severe defects of T-cell responses and homeostasis. Accordingly, we and others have documented proofs of a systemic immune dysregulation in CLL patients, including increased circulating T cell numbers with disease stage, imbalanced Th1/Th2 profiles, increased circulating numbers of regulatory phenotypes, and reduced B-cell capacity for antigen presentation, among others, which may lead to immunodeficiency or autoimmune manifestations related to the disease [1,2]. Additionally, hepato-and splenomegaly and the occurrence of enlarged lymph nodes (LN) with various localizations are considered the most frequent clinical manifestations in B-CLL patients [3].…”
Section: Introductionmentioning
confidence: 98%